Analysis of Business Strategy and Entrepreneurial Motivation in Small Businesses in Indonesia - lamin, lamin (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (Adpebi), 2022)
This study aims to determine the impact of business strategy and entrepreneurial motivation on the performance of small businesses in the city of Pekanbaru. In this study, data were collected through questionnaires to 95 motorcycle repair business owners in the city of Pekanbaru. The data analysis technique used is simple regression analysis which serves to prove the research hypothesis. Partially, business strategy has a significant effect on the performance of small businesses in the city of Pekanbaru. And also entrepreneurial motivation has a significant effect on the performance of small businesses in the city of Pekanbaru. Based on the results of multiple regression, it can be concluded that the business strategy and entrepreneurial motivation variables together have a significant influence on the small business performance variables in the city of Pekanbaru.